Cymbopogon Nardus From Malay Society Tradition Perspectives An Analysis of Chemical Composition Using Steam Distillation From Scientific Finding - Nurulwahidah Fauzi; Juliana Jumal (USIM Press, 2024)
Vol. 31 (2020): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [August 2020]